A novel association of BoLA DRB3 alleles in BLV infected cattle with different proviral loads - Nieto Farias, María Victoria (2017)
Bovine leukemia virus (BLV) is associated with the most common neoplastic disease of cattle. BLV has a silent dissemination in the herd due to infected cell exchange, thus the concentration of BLV-infected cells in blood should play a major role in the success of viral transmission. Genes from Bovine leukocyte antigen (BoLA), the MHC system of cattle, are associated with genetic resistance and susceptibility to a wide range of diseases, and also with production traits. Some BoLA DRB3.2 allele polymorphisms in Holstein cattle have been associated with resistance or susceptibility to BLV-disease development, or with proviral load (PVL). This investigation studied 107 BLV-infected Argentinean Holstein dairy cows, all of them belonging to one herd. PVL was analysed by qPCR and animals were classified as high proviral load (HPVL, N = 88) and low proviral load (LPVL, N = 19), and BoLA DRB3.2 alleles were genotyped. Alleles BoLA DRB3.2*1501 and *1201 were significantly associated with HPVL (p = 0.0230 and p = 0.0111 respectively), while allele BoLA DRB3.2*0201 was significantly associated with LPVL (p = 0.0030). The present study aims at contributing to the knowledge of the association between BoLA polymorphism and development of a BLV infection profile. Genes that best explain the PVL in this population resulted BoLA DRB3.2*0201 (as a protection factor) and *1501 (as a risk factor). Allelic differences may play an important role in the development of effective immune responses. A better understanding of how BoLA polymorphism contributes to these responses and the establishment of a BLV status is desirable to schedule and evaluate control measures.